Identification of Customary International Law and Other Topics: The Sixty-Seventh Session of the International Law Commission. Issue 4 (October 2015) - Murphy, Sean D.
Abstract : The International Law Commission held its sixty-seventh session in Geneva from May 4 to June 5, and from July 6 to August 7, 2015, under the chairmanship of Narinder Singh (India). Notably, the Commission's drafting committee completed a full set of sixteen draft conclusions on the topic of identification of customary international law, paving the way for those conclusions with commentaries to be approved by the Commission on first reading in 2016.